2023
DOI: 10.1007/s10549-023-06941-z
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic and socioeconomic differences in breast cancer surgery performed and delayed treatment: mediating impact on mortality

Abstract: Although Socioeconomic status (SES), race/ethnicity, and surgical type/delays are associated with breast cancer mortality outcomes, studies on these associations have been contrasting. This study examined the racial/ethnic and SES differences in surgical treatment types and delays. Also, we quanti ed the extent to which these differences explained the racial/ethnic disparities in breast cancer mortality. MethodsWe studied 290,066 women 40 + years old diagnosed with breast cancer between 2010 and 2017 identi ed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…When we consider both sexes, breast cancer was the most frequent type of cancer in our series, this result being similar to those in the literature[ 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…When we consider both sexes, breast cancer was the most frequent type of cancer in our series, this result being similar to those in the literature[ 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…In our study, BC patients from affluent neighborhoods received more surgical and radiation treatments which can be explained by the higher percentages of urban areas in these regions with better facilities for treatments, and better referral systems. In a study by Fwelo et al, it was found that Black and Hispanic women were more likely to undergo mastectomy compared to Whites [ 29 ]. This discrepancy could be attributed to the fact that breast cancer is often diagnosed when locally advanced in Black women, indicating limited access to early detection through adequate screening and precluding lumpectomy [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Fwelo et al, it was found that Black and Hispanic women were more likely to undergo mastectomy compared to Whites [ 29 ]. This discrepancy could be attributed to the fact that breast cancer is often diagnosed when locally advanced in Black women, indicating limited access to early detection through adequate screening and precluding lumpectomy [ 27 , 29 ]. Additionally, cultural preferences, low healthcare literacy, and transportation barriers may contribute to limited healthcare access, potentially influencing the decision to avoid radiation treatment [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Goel et al report that a lower neighborhood socioeconomic status is associated with a shorter breast cancer-specific survival, even after controlling for individual sociodemographic, access to care, comorbidities, tumor characteristics, and the National Comprehensive Cancer Network (NCCN) treatment paradigms [46]. Furthermore, non-Hispanic Black patients and Hispanic patients are more likely to undergo mastectomies and receive delayed treatment than non-Hispanic White patients [47]. Digital health platforms can provide important education to patients who may have difficulty accessing care otherwise.…”
Section: Discussionmentioning
confidence: 99%